THE EFFECTIVENESS OF A NATURAL PREPARATION IN THE TREATMENT AND PREVENTION OF INFLUENZA AND OTHER ACUTE RESPIRATORY DISEASES IN CHILDREN - O. V. Shamsheva; V. F. Uchaikin (LLC "Diagnostics and Vaccines", 2017)
The results of application of the drug of natural origin (Aflubin) with immunomodulating, anti-inflammatory, detoxifying effect in complex treatment of influenza and acute respiratory infections in children are presented. The inclusion of Aflubin in the complex treatment of diseases contributed to reducing the severity and duration of intoxication, reducing the duration of catarrhal phenomena, preventing the development of secondary bacterial complications. Relative simplicity of the drug (drops) at affordable cost, therapeutic and preventive efficacy in all age groups ensure its high compliance.